Exploration of Medicinal Plant Potential in the Semende Tribe Community in South Ogan Komering Ulu - Ulmillah Aulia; Saputri Dwijowati Asih; Aprianti Pegi; Pawhestri Suci Wulan; Alkausar Triawan; Satitiningrum Yuni (E3S Web of Conferences, 2024)
The Semende tribe in Sebaja Village, Sungai Are Sub-district, South Ogan Komering Ulu Regency, still uses medicinal plants to treat various types of illnesses. This research aims to identify the types of plants used, their utilization methods, and assess the conservation status of the medicinal plants utilized by the Semende tribe in Sebaja Village, Sungai Are Sub-district, South Ogan Komering Ulu Regency. This study employs a qualitative approach with a descriptive method. Data were collected through observation, interviews with key informants (traditional healers), non-key informants (community members), and documentation collection. Sampling techniques included purposive sampling and snowball sampling. The research findings were analyzed descriptively. From the research results, it was discovered that the Semende tribe in Sebaja Village, Sungai Are Sub-district, South Ogan Komering Ulu Regency, utilizes 30 types of medicinal plants in traditional medicine. The Semende tribe employs various methods such as boiling, heating, pounding, and others in the use of these plants. The conservation status of each medicinal plant, based on the International Union for the Conservation of Nature (IUCN) categories, shows variation, with some plants classified as Near Threatened (NT) and the majority falling into the Least Concern (LC) category in terms of conservation status.